Aromatic ointments for the common cold: what does the science say? - Andrew Smith; Oliver Matthews (BioExcel Publishing Ltd, 2022)
Background: Upper respiratory tract infections occur with an annual incidence of 17.2 billion cases globally. The negative impact that symptoms have on sleep is thought to slow the recovery process. Plant-derived aromatics have been used since ancient times to treat respiratory illnesses. In this narrative review, we summarize the use of aromatics for the symptomatic relief of upper respiratory tract infections and how this affects sleep quality. Methods: Literature searches were conducted using a series of search terms and results were screened for relevance. Additional references were included according to the expert knowledge of the authors. Discussion: Multiple studies have observed that essential oil mixtures of aromatics enhance symptom relief for upper respiratory tract infections and their inhalation has been reported to have antitussive effects. Clinical trials assessing the efficacy of an ointment containing menthol, eucalyptus and camphor found patients to experience faster nasal cooling and decongestion times. Treatment with the same ointment also resulted in significant improvements in reported sleep quality. Aromatic treatment did not improve objective nasal airway measures in any of the studies. Conclusion: Whilst not affecting objective measures of nasal airway resistance, the use of aromatics leads to improvements in a number of subjective sensations associated with the common cold. Such benefits result in better sleep, which likely aids recovery. Therefore, aromatics remain a well tolerated and effective option for the symptomatic relief of upper respiratory tract infections.